f(x) = 3x-5 and g(x) = x-10 f(-3) g(22) (f - g)(-3) (g + f)(8)

f(x) = 3x-5 and g(x) = x-10 f(-3) g(22) (f - g)(-3) (g + f)(8)

G(n)=3n+5 find (g•g)(2)

Perform the operations: {a,G}\{*,11} Could someone help? Is it all of them?

P(t)=34,178,000+78,000t and its health care costs are given by C(t)=47,863,000+430,500t+178t2 (a) Create the function representing the state's per capita health care costs (b)...

given the following data what would be the forecast for period 5 using the 3 month weighted average with weights of .5 - .3 - .2 using .5 for the most recent data 128 140 130

Given n(x)=x2-9 m(x)=x+3 p(x)=sqrt(x+1) Use the functions to find: a. (n-m)(-6) b...

Given m(x)=x+3, p(x)=sqrt(x+1) Find (m*p)(x) and write the domain of m*p in interval notation.

g(x)=2x and h(x)=x-3. find (gh)(-4)

if f(x)=6x squared+37x+35 and g(x)=x+5 find (f over g)(x)

Company 1 charges $1.50/km and a daily fee of $45. Company 2 charges $1.65/km and a daily fee of $40. What is the difference in price between the two companies? Use composite functions...

The problem is h(x)=2/5x-4 Please help guide me through this.

The answer choices are A)x^2+1 B)x-1 C)x+2/2 D)-x+2/2 I picked A as the right answer but I'm not sure.

I got -8n^3-6n+4 as a solution, but none of those choices have that as the answer. What did i do wrong?

Please guide me through this.

Please help guide me through this. I don't even know the first step.

Please guide me through this. Am I supposed to plug in the (x+3) after putting 3x+3/x^2-3x ?

What am I supposed to do with that n/2 ?

How would you solve this f(x)⁄g(x) problem (please include ALL steps and an explanation for each)? f(x)=(5x+11)/(x2-9) g(x)= (4x-2)/(x2-9) Also, would...